On the moduli spaces of framed logarithmic connections on a Riemann surface - Biswas, Indranil; Inaba, Michi-aki; Komyo, Arata; Saito, Masa-Hiko (Comptes rendus. Mathématique, 2021)
We describe some results on moduli space of logarithmic connections equipped with framings on a $n$-pointed compact Riemann surface.